Stratigraphic Architecture of the Karoo River Channels at the End-Capitanian - Bordy, Emese M.; Paiva, Francisco (Frontiers in Earth Science, 2021)
The main Karoo Basin of southern Africa contains the continental record of the end-Triassic, end-Permian and end-Capitanian mass extinction events. Of these, the environmental drivers of the end-Capitanian are least known. Integrating quantitative stratigraphic architecture analysis from abundant outcrop profiles, palaeocurrent measurements and petrography, this study investigates the stratigraphic interval that records the end-Capitanian extinction event in the southwestern and southern main Karoo Basin and demonstrates that this biotic change coincided with a subtle variation in the stratigraphic architectural style ~260 Ma ago. Our multi-proxy sedimentological work not only defines the depositional setting of the succession as a megafan system that drained the foothills of the Cape Fold Belt, but also attempts to differentiate the tectonic and climatic controls on the fluvial architecture of this palaeontologically important Permian succession. Our results reveal limited changes in sediment sources, palaeocurrents, sandstone body geometries and possibly a constant hot, semi-arid palaeoclimate during the deposition of the studied interval; however, the stratigraphic trends show upward increase in: 1) laterally-accreted, sandy architectural elements, and 2) architectural elements that build a portion of the floodplain deposits. We consider this to reflect a long term retrogradational stacking pattern of facies composition that can be linked to changes on the medial parts of southward draining megafans, where channel sinuosity increased, and depositional energy decreased at the end-Capitanian. The shift in the fluvial architecture was likely triggered by basin-wide allogenic controls rather than local autogenic processes, because this trend is observed in the coeval stratigraphic intervals from geographically disparate areas in the southwestern and southern main Karoo Basin. Consequently, we propose that this regional backstepping most likely resulted from tectonic events in the adjacent Cape Fold Belt.